PENGARUH INTELLECTUAL CAPITAL TERHADAP PRODUKTIVITAS PERBANKAN DI INDONESIA - Winanda Warga Dalam; Siti Nurfaizah (Jurnal Ekonomi Bisnis Manajemen Prima, 2022)
This study examines whether banking productivity as proxies by ATO and EP is not influenced by intellectual capital. Purposive sampling is used in the sampling technique of the banks listed on the Indonesia Stock Exchange for the 2015-2019 period which is the archival data in this study. The total sample is 105 data obtained from 21 companies for 5 years. This study uses panel data regression analysis. The results showed that intellectual capital had an effect on ATO and EP. VAHU has no effect on ATO and EP, VACA has no effect on ATO and EP, STVA has no effect on ATO and EP. This research is limited to the banking sector listed on the Indonesia Stock Exchange.